The Paradox of Trauma and Growth in Pastoral and Spiritual Care: Night Blooming - Werdel, Mary Beth (Lexington Books, 2023)
The Paradox of Trauma and Growth in Pastoral and Spiritual Care: Night Blooming introduces and bridges the gap between the psychological and spiritual perspectives and responses in trauma work, illuminating the complexity of the human phenomenon of growth though suffering that is too easily misunderstood in the context of pastoral and spiritual care. Through the hopeful metaphor of night bloomers, rare plants that grow because of light, but bloom in the darkness, it is suggested that while psychological trauma is inherently negative, and suffering creates a spiritual inner night, moving through it may reveal a new, complex reality of the human experience not previously understood. We may see ourselves, others, or the world in a way that is stronger, wiser, deeper, or more brilliant than we had known before. The book presents the goal of pastoral and spiritual work is not to extinguish darkness. Nor is it to solely focus on the light. The work is to learn how to stay awake through the night, without glorifying it. Such a task is far easier when we believe there might be a rare and uniquely beautiful bloom to stay awake for, and that witnessing such a bloom could have great consequences for living a meaningful life.